Gender, religion, and diversity cross-cultural perspectives (Continuum, 2004)
"Gender Relation and Diversity provides an introduction to some of the most challenging perspectives in the contemporary study of gender and religion. This book is the outcome of an international collaboration between a wide range of researchers from different countries and fields of religious studies. The range and diversity of their contributions is the very strength of this book, for it shows how gendering works in studying different religious materials, whether foundational texts from the Bible or Koran philosophical ideas about truth, essentialism, history or symbolism, the impact of French feminist thinkers such as Irigaray or Kristeva, or again critical perspectives dealing with the impact of race, gender, and class on religion, or by deconstructing religious data from a postcolonial critical standpoint or examining the impact of imperialism and orientalism on religion and gender."--BOOK JACKET.